1984
DOI: 10.1002/chin.198446003
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: GAMMA RAY INDUCED DECOMPOSITION OF ALKALI METAL NITRATES

Abstract: Die durch "Coy‐Strahlung induzierte Zers. der Alkalimetallnitrate unter Bildung von N03′ und O3 wird über einen weiten Bereich absorbierter Dosis untersucht.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2005
2005
2005
2005

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…All other admixtures follow similar trend. This behaviour is similar to that observed in the case of most of the alkali metal and other metal nitrates (Kulkarni and Garg, 1984;Muhammad and Maddock, 1978). This is essentially due to predominance of the back reaction or radiation annealing, which reduces the rate of formation of nitrite at higher doses (Johnson, 1970).…”
Section: Article In Presssupporting
confidence: 63%
See 1 more Smart Citation
“…All other admixtures follow similar trend. This behaviour is similar to that observed in the case of most of the alkali metal and other metal nitrates (Kulkarni and Garg, 1984;Muhammad and Maddock, 1978). This is essentially due to predominance of the back reaction or radiation annealing, which reduces the rate of formation of nitrite at higher doses (Johnson, 1970).…”
Section: Article In Presssupporting
confidence: 63%
“…It has been observed that G(NO 2 À ) values increase with the charge on outer cation and the size of cation, especially in the case of pure alkali and alkaline earth metal nitrates (Joshi and Garg, 1994a, b;Kulkarni and Garg, 1984;Agrawal and Garg, 1998). Boldyrev (1971) studied the effect of doping Tl + , Sr 2+ , Pb 2+ , Ce 3+ , La 3+ , Pr 3+ and Nd 3+ ions on the radiolytic decomposition of KNO 3 and reported that the radiation yield increased due to formation of defects in the lattice.…”
Section: Introductionmentioning
confidence: 97%